Moving toward environmental sustainability: assessing the influence of geothermal power on carbon dioxide emissions - Alsaleh, Mohd; Yang, Zhengyong; Chen, Tinggui; Wang, Xiaohui; Abdul Rahim, Abdul Samad; Mahmood, Haider (Elsevier, 2023)
The primary objective of this study is to investigate the effect of geothermal energy output on carbon dioxide emissions among the European countries (EU) classified as EU27 states, within the time frame 1990 to 2021. The study adopted autoregressive-distributed lag (ARDL), and the findings show that the carbon dioxide emissions mitigate with an improvement in geothermal power production. Carbon dioxide emissions were observed to be increased by some socioeconomic factors such as population density, economic growth, and fossil fuel. Findings from this study show there could be a significant reduction in carbon dioxide emission among the EU13 emerging economies leveraging on geothermal energy growth than what will be achieved among the EU14 emerged economies. Conversely, the findings from this study also show that a significant level of reduction could be attained in carbon dioxide emission among the EU14 emerged economies as a result of aging population density than we could have among the EU13 emerging economies. Also, this study established that EU14 emerging economies could attain a significant increase in carbon dioxide emissions through fossil fuel consumption and economic growth than what will be attained among the EU13 emerging economies. The three estimators adopted in the study which are the pooled mean group, mean group, and dynamic fixed effect confirmed that the projected calculations in the study are confirmed valid. This study, therefore, recommended that European nations classified as EU27 should lay more emphasis on geothermal growth to attain energy and environmental goals. Legislators in these EU countries should focus more on policies that will ensure the security and sustainability of geothermal growth. Policymakers in these EU countries should make concerted efforts toward making policies that will promote the growth and sustainability of geothermal power, thereby cutting down the need for fossil fuel and CO2 emissions in the future time.